Tratamento anaeróbio de efluente de fecularia em reator horizontal de uma fase - Kuczman, Osvaldo (2007)
The grouping of cassava starch production factories at northwest/west Paraná regions, Mato Grosso do Sul and São Paulo region has led to a million daily income of wastewater, which, treated at stabilization lagoons, generates greenhouse gases, unpleasant odors and landscape s degradation. The current research has evaluated the anaerobic digestion of waste cassava starch in one-phase horizontal reactor, having a 16,2 L volume, operated at 33 ± 1°C with manipueira having organic load rates of 1,28, 1,57, 2,68 and 1,18 g COD L- 1reactor day-1 for the Hydraulic Retention Times (HRT) being the experiment realization order of 12,96, 8,27 6,59 and 15,00 days, respectively. The feeding has been continuous, approaching to the real production s conditions. The cycle evaluation, for each HRT, lasted 15 days, revealing that the time didn t interfere, within 5%. The average removal in Total Solids (TS) is 98 and 77 %, Volatile Solids (VS) 99 and 90%, organic loads 96 and 95%, having as biogas yielding 0,817 and 0,604 L gas g-1 COD removed at the 8, 27 and 6,59 days, respectively. However, the most homogeneous removals in TS and VS occurred at the 12,96 and 8,27 days, not following the COD removals. The best average specific production for biogas ranged from 0,654 to 0,627 L gás L-1r d-1, verified in TRH 8,27 and 6,59 days. The average biogas methane content, come from the 15,00 days HRT, was 58,85%. The average relation Volatile Acidity/Total Alkalinity situated from 0,14 to 0,30. By the obtained results, it was concluded that it is possible to reduce the organic load of waste cassava starch through anaerobic digestion in one-phase horizontal reactor for the conditions established at the present study.